Prevalence of respiratory symptoms and associated factors among sanitation workers in Sub Saharan Africa: a systematic review and meta-analysis - Berihun, Gete; Desye, Belay; Berhanu, Leykun; Daba, Chala; Walle, Zebader; Geto, Abebe Kassa (Frontiers in Public Health, 2025)
IntroductionOccupational health problems are the major issues of the world, particularly in developing countries. Sanitation workers are facing various health problems with little attention while conducting their day today activities. The review emphasizes the critical need for policies that ensure safety standards, provide proper protective gear, and establish regular health monitoring to protect workers’ health and wellbeing.ObjectiveThe aim of the study was to assess the prevalence of respiratory symptoms and associated factors among sanitation workers in Sub-Saharan Africa.Methods and materialsThis systematic review and meta-analysis was done based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA 2020). Literatures were searched using various database like Google scholar, Science-Direct, Pub-Med (Medline), Hinari, and Google. From eligible studies, data was extracted using Microsoft excel and exported to STATA version 14 statistical software for analysis. The prevalence of respiratory symptom was estimated using a random effect model. Publication bias was determined using Egger test and funnel plot whereas heterogeneity was evaluated using I2. Fortunately, 13 studies were included with a total participants of 4,401.ResultsThe pooled prevalence of respiratory symptoms among sanitation workers was 43.79% (95% CI: 35.26, 52.33; I2 = 97.3%, p < 0.000). Sanitation workers with a history of respiratory illness were 4.16 times more likely to have had respiratory symptoms compared to those without a history (OR: 4.16, 95% CI: 2.67, 5.66). Additionally, sanitation workers who did not wear nose/mouse masks were 2.36 times more likely to experience respiratory symptoms compared to their counterparts (OR: 2.36, 95% CI: 1.40, 3.32). Moreover, Sanitation workers with working experiences of greater than five were 1.81 times more likely to experience respiratory symptoms than those with less than 5 years working experiences (OR: 1.81, 95% CI: 1.26, 2.39).ConclusionGenerally, half of the sanitation workers experienced respiratory symptoms. The symptoms were associated with history of respiratory illness, utilizing of nose/ mouth face mask and working experience. Hence, awareness creation session should conducted mainly for those with history of respiratory illness and poor personal protective users.